A compact MIMO antenna with high gain and dual circular polarization using a T divider for WLAN applications - Dat Tran-Huy; Nguyen Tran-Viet-Duc; Hung Tran; Niamat Hussain (Scientific Reports, 2025)
Abstract This paper presents a circularly polarized (CP) multiple-input multiple-output (MIMO) antenna with compact size and high-gain features for wireless local area network (WLAN) applications. The proposed approach employs two compact dual-CP antennas and T-junction power dividers to design 2-port MIMO antenna. The use of T-junction divider can excite both radiators simultaneously, resulting in high gain operation. For validation, an antenna prototype with overall dimensions of 1.06 $$λ$$ $$×$$ 0.65 $$λ$$ $$×$$ 0.03 $$λ$$ at 2.45 GHz is fabricated and measured. The measured operating bandwidth is from 2.43 to 2.485 GHz, in which the matching is less than $$-10$$ dB, the isolation is higher than 10 dB, and the axial ration is smaller than 3 dB. Additionally, the antenna also performs high gain radiation of about 8.0 dBi and good MIMO diversity performance in terms of envelop correlation coefficient, diversity gain, and so on. In comparison with the related works, the proposed antenna is beneficial in terms of CP radiation and overall dimensions with less number of required radiating elements, while achieving comparable performance.